The application and interpretation of the two-parameter item response model in the context of replicated preference testing - Button, Zach (Kansas State University, 2015)
Preference testing is a popular method of determining consumer preferences for a variety of products in areas such as sensory analysis, animal welfare, and pharmacology. However, many prominent models for this type of data do not allow different probabilities of preferring one product over the other for each individual consumer, called overdispersion, which intuitively exists in real-world situations. We investigate the Two-Parameter variation of the Item Response Model (IRM) in the context of replicated preference testing. Because the IRM is most commonly applied to multiple-choice testing, our primary focus is the interpretation of the model parameters with respect to preference testing and the evaluation of the model’s usefulness in this context. We fit a Bayesian version of the Two-Parameter Probit IRM (2PP) to two real-world datasets, Raisin Bran and Cola, as well as five hypothetical datasets constructed with specific parameter properties in mind. The values of the parameters are sampled via the Gibbs Sampler and examined using various plots of the posterior distributions. Next, several different models and prior distribution specifications are compared over the Raisin Bran and Cola datasets using the Deviance Information Criterion (DIC). The Two-Parameter IRM is a useful tool in the context of replicated preference testing, due to its ability to accommodate overdispersion, its intuitive interpretation, and its flexibility in terms of parameterization, link function, and prior specification. However, we find that this model brings computational difficulties in certain situations, some of which require creative solutions. Although the IRM can be interpreted for replicated preference testing scenarios, this data typically contains few replications, while the model was designed for exams with many items. We conclude that the IRM may provide little evidence for marketing decisions, and it is better-suited for exploring the nature of consumer preferences early in product development.
Keywords: Item response theory; Replicated preference testing; Bayesian; Gibbs sampling; Statistics (0463)